2003
DOI: 10.1152/ajpcell.00223.2002
|View full text |Cite
|
Sign up to set email alerts
|

Dual effect of nitric oxide on cytosolic Ca2+concentration and insulin secretion in rat pancreatic β-cells

Abstract: Kaneko, Yukiko, Tomohisa Ishikawa, Satoshi Amano, and Koichi Nakayama. Dual effect of nitric oxide on cytosolic Ca 2ϩ concentration and insulin secretion in rat pancreatic ␤-cells. Am J Physiol Cell Physiol 284: C1215-C1222, 2003. First published January 15, 2003 10.1152/ajpcell.00223.2002In isolated rat pancreatic ␤-cells, the nitric oxide (NO) donor NOC-7 at 1 M reduced the amplitude of the oscillations of cytosolic Ca 2ϩ concentration ([Ca 2ϩ ]c) induced by 11.1 mM glucose, and at 10 M terminated them. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
40
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 40 publications
9
40
1
Order By: Relevance
“…For example, Wohlfart et al (33) and Hwang et al (34) found that activation of guanylyl cyclase stimulated an NO synthesis and release in endothelial cells, which is independent of the elevation of cyclic GMP but strictly dependent on calcium. Consistently, 8-bromo-cGMP is also found to increase the amplitude of the Ca 2ϩ oscillations (35). Other studies (36,37) found that cGMP has two distinct effects on the Ca 2ϩ : a facilitation of the Ca 2ϩ influx through L-type voltage-operated Ca 2ϩ channels and an acceleration of the Ca 2ϩ sequestration in the endoplasmic reticulum.…”
Section: Discussionsupporting
confidence: 56%
“…For example, Wohlfart et al (33) and Hwang et al (34) found that activation of guanylyl cyclase stimulated an NO synthesis and release in endothelial cells, which is independent of the elevation of cyclic GMP but strictly dependent on calcium. Consistently, 8-bromo-cGMP is also found to increase the amplitude of the Ca 2ϩ oscillations (35). Other studies (36,37) found that cGMP has two distinct effects on the Ca 2ϩ : a facilitation of the Ca 2ϩ influx through L-type voltage-operated Ca 2ϩ channels and an acceleration of the Ca 2ϩ sequestration in the endoplasmic reticulum.…”
Section: Discussionsupporting
confidence: 56%
“…11 Similarly, reactive nitrogen species (RNS) have beneficial or detrimental effects on b-cell function depending on their levels. 12 In agreement with this tenet we show here that massive ROS/RNS production by photoactivation of AlClPc at maximal (100%) LED intensity abolished Ca 2C oscillations in MIN6 b-cells (Fig. 2), while moderate ROS/RNS production (10% LED) accelerated the periodic Ca 2C excursions (Fig.…”
Section: Discussionsupporting
confidence: 86%
“…10 Hence, ROS may act as a double-edged sword: moderate and short-term elevations play a positive signaling role augmenting insulin secretion, but prolonged exposure to elevated ROS levels, characteristic of oxidative stress, are detrimental for the b-cells. 9,11 Similarly, reactive nitrogen species (RNS), such as nitric oxide (NO), have been shown to elevate Ca 2C levels and stimulate insulin secretion at low concentrations, 12 whereas high NO concentrations exert an inhibitory effect on b-cell function 12 and survival. 13 ROS/RNS target various cellular mechanisms underlying insulin secretion, 9 and in particular components involved in Ca 2C handling.…”
Section: Introductionmentioning
confidence: 99%
“…It is likely that the timing and level of NO production in the healing wound must be carefully balanced to ensure a beneficial effect. [39][40][41][42] This work also demonstrated that human tendon cells have the capacity to synthesize physiologically active NO following transfection of iNOS gene via adenovirus.…”
Section: Discussionmentioning
confidence: 93%